2013
DOI: 10.3928/01477447-20131120-20
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Lysis of Adhesions for Stiff Total Knee Arthroplasty

Abstract: The goal of this study was to evaluate the efficacy of arthroscopic lysis of adhesions after total knee arthroplasty (TKA) in improving range of motion (ROM) and providing an improvement in knee function. The authors retrospectively examined 19 patients who underwent arthroscopic lysis of adhesions following TKA due to poor ROM. The criterion for lysis was the inability to flex to 90° at 3 months. All patients were followed for at least 2 years after lysis. Patient demographics, postoperative and follow-up ROM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…Other studies have reported improvements in knee scores following LOA for the stiff total knee arthroplasty. 28,29 Despite these findings, no previous study has examined improvements in functional knee scores following LOA in the stiff knee after ligamentous reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have reported improvements in knee scores following LOA for the stiff total knee arthroplasty. 28,29 Despite these findings, no previous study has examined improvements in functional knee scores following LOA in the stiff knee after ligamentous reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…9 The remaining studies found suitable for inclusion were scored on a scale of 0 to 100 based on 11 different standards from the CMS. [10][11][12][13][14][15][16]…”
Section: Data Collectionmentioning
confidence: 99%
“…[11][12][13][14]16 Following arthroscopic arthrolysis, the mean final follow-up time from all included studies was 24.8 months (range 1-124 months; ►Table 5). [10][11][12][13][14][15][16]…”
Section: Follow-upmentioning
confidence: 99%
“…Post-traumatic contracture can result from either an initial injury to the joint or as a complication from surgery on the joint, such as anterior cruciate ligament (ACL) reconstruction or total knee arthroscopy (TKA) (Cosgarea et al, 1994). Currently when patients have joint contracture due to arthrofibrosis they will receive either conservative treatment or in more severe cases, surgery to release the contracture, however a complete recovery is not always attained (Enad, 2014, Hutchinson et al, 2005, Schiavone Panni et al, 2009, Schwarzkopf et al, 2013, Kucera et al, 2007, Cosgarea et al, 1994.…”
Section: Introductionmentioning
confidence: 99%